Can Personality Bridge the Intention-behavior Gap to Predict Who Will Exercise? - MacCann, C.; Todd, J.; Mullan, Barbara; Roberts, R. (PNG Publications, 2015)
Objectives: To explore whether HEXACO personality domains could incrementally increase the prediction of exercise behavior above Theory of Planned Behavior (TPB) variables, and whether personality moderated the intention behavior gap. Methods: US College students (N = 1017) completed demographic, TPB, HEXACO domain and exercise behavior measures. Results: The TPB predicted physical activity, accounting for 45% and 39% of variance in intention and behavior, respectively. Regarding personality domains, lower emotionality significantly predicted intention, and lower honesty-humility significantly predicted behavior, but these were small effects. Personality did not moderate the intention-behavior gap. Conclusions: Personality has a limited direct role in predicting exercise intention and behavior beyond the TPB. The prediction of exercise behavior from honesty-humility highlights the importance of considering the HEXACO personality model.